PENERAPAN STRATEGI INDEX CARD MATCH DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS V MIN 3 TAPANULI SELATAN - Lubis, Maulana Arafat; Azizan, Nashran (Jurnal Ilmiah Al-Hadi, 2018)
The objective of the study was to find out the result of students’ ability before and after the implementation of index card match strategy and to evaluate whether index card match strategy able to improve student’s ability in learning the topic Indonesian Independence Day proclamation. Action research is applied in this study. The subject was the fifth students of MIN 3 Tapanuli Selatan academic year 2017/2018. The object of the study was index card match strategy to improve student’s ability in learning Indonesia Independence Day proclamation as social science subject. The instruments of the study were test, observation, documentation and interview. The data were analyzed by using data reduction, data display and verifying/conclusion. Before index card match strategy was implied, the result of the study was low. The percentage of minimal standard mastery was 27,27% with the average 56,06. After index card match strategy was implied, the percentage was improved. The percentage reached 63,63% and67,12 at the end of the first cycle. Then, at the end of the second cycle, the improvement reached 90,9% and 76, 36. It can be concluded that the implementation of index card match strategy was able to improve students’ ability for the topic Indonesia Independence day proclamation at the fifth grade students of MIN 3 Tapanuli Selatan academic year 2017/2018.